1984
DOI: 10.1177/030098588402100303
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Functional Rat Adrenal Medullary Pheochromocytomas

Abstract: In this study of 29-month-old male Fischer and Sprague-Dawley rats, the tumor pheochromocytoma occurred in seven of 20 Fischer rats (35%) and ten of 22 Sprague-Dawley rats (45%). Mean blood pressures and mean urinary vanillylmandelic acid levels of rats with pheochromocytomas did not vary significantly from rats with no tumors. Pheochromocytoma in our rats generally was non-functional or of minimal clinical significance. The content of chromaffin granules in tumor cells varied from abundant to not detectable, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Although serum or urine catecholamine or catecholamine metabolite levels were not available for the animals studied, biochemically functional tumors frequently do not produce detectable elevations of circulating catecholamines if their secretory activity is low, as is apparently often the case for pheochromocytomas in rats. 27 In this study, we did not stain for DBH and therefore cannot be certain whether tumors that were TH-positive but PNMT-negative produced norepinephrine or dopamine. Studies of both human19.22 and rat38 adrenal glands, however, have shown that most pheochromocytomas that are positive for TH are also positive for DBH.…”
Section: Discussionmentioning
confidence: 81%
“…Although serum or urine catecholamine or catecholamine metabolite levels were not available for the animals studied, biochemically functional tumors frequently do not produce detectable elevations of circulating catecholamines if their secretory activity is low, as is apparently often the case for pheochromocytomas in rats. 27 In this study, we did not stain for DBH and therefore cannot be certain whether tumors that were TH-positive but PNMT-negative produced norepinephrine or dopamine. Studies of both human19.22 and rat38 adrenal glands, however, have shown that most pheochromocytomas that are positive for TH are also positive for DBH.…”
Section: Discussionmentioning
confidence: 81%
“…Several studies suggest that the development of adrenal medullary hyperplasia and pheochromocytomas in rats is accompanied by increasing NE/E ratios (Bär, 1988;Bosland and Bär, 1984;Eränkö , 1955;Ribelin et al, 1984 andTischler et al, 1985). Rat pheochromocytomas appear, in most instances, to have a distinctive phenotype characterized by predominant or exclusive production of NE and by secretory granules smaller and sparser than those in typical E and NE cells (Figure 8) (Tischler et al,Figure 7 Rat adrenal gland with 'malignant' pheochromocytoma.…”
Section: Functionmentioning
confidence: 99%
“…Catecholaminesynthesizing ability can almost invariably be demonstrated by other more sensitive methods (Bosland and Bär, 1984;Eränkö , 1955;Ribelin et al, 1984;Tischler et al, 1985 andTischler et al, 1990). However, this is no longer an issue.…”
Section: ) the Resemblance Of Tumor Cells To Immature Chromaffinmentioning
confidence: 99%
“…Glucocorticoids (GCs) play an important role in stress and immunity (Griffin et al , ). As adrenal is the most sensitive endocrine organ to toxic insults, GC production becomes a target in adrenal toxicity (Ribelin et al , ). Studies have revealed a range of chemicals with the potential to cause adrenal toxicity altering the biosynthesis, secretion, transport, metabolism and binding of GCs (Harvey, ).…”
Section: Introductionmentioning
confidence: 99%